Prospect of Natural Fiber as Source of Currency Paper - SUDJINDRO, . (Perspektif, 2011)
Several types of plants producing natural fiber, such as fruit fiber (cotton), stems (kenaf, roselle, yute, flax, linum), and leaf (abaca, agave) have long been cultivated in Indonesia. They have even a solid status as raw material for industry nationally and internationally, such as cotton, kenaf, abaca, and flax. Plants of these natural fibers are potential for use as raw material for pulp and paper, and other industrial raw materials. Each year, Indonesia imports about 1.7 reem of currency paper worth of ± US$ 50 million or equivalent to ± Rp475 billion. High quality raw materials for currency paper are from cotton fibers (linters) mixed with other natural fibers, such as abaca, ramie, kenaf, and linum in a particular composition. Local natural fibers have great potential to be utilized as an alternative to meeting the needs of the domestic currency paper material. Balai Besar Pulp dan Kertas has carried out many research on the currency paper materials. Bank of Indonesia in collaboration with LIPI, Balittas, ITS, and the Ministry of Industry and Trade (Kemperindag) has considered that the genetic material of plants, land and human resources are already highly supportive to conduct the business of natural fibers plantation. If the business can maximally be empowered domestic sources, it may be able to improve farmers’ welfare through agribusiness of natural fiber commodities. This business in turn may reduce the imports of currency paper and save foreign exchange, as well. Empowerment of flooded and acidic lands outside Java, by planting high yielding varieties, is a positive effort to improve farmers’ welfare on these marginal lands.Keywords : Raw material, currency paper, natural fibers, pulp and paper, farmers’ prosperity.